Наука України у світовому інформаційному просторі - Мриглод, І.М.; Мриглод, О.І. (№10, 2007)
The problem of advanced information technologies use for national scientists inclusion into world scientific community is reviewed. Existing quantitative criteria of science evaluation and expediency of their implementation in our country are investigated. Based on open electronic database analysis the conclusion is made on insufficient presentation of Ukrainian science in internet space.